Differential expression of immunity-related genes in larval Manduca sexta tissues in response to gut and systemic infection - von Bredow, Yvette M.; Prochazkova, Petra; Dvorak, Jiri; Skanta, Frantisek; Trenczek, Tina E.; Bilej, Martin; von Bredow, Christoph-Rüdiger (Frontiers in Cellular and Infection Microbiology, 2023)
The midgut epithelium functions as tissue for nutrient uptake as well as physical barrier against pathogens. It responds to pathogen contact by production and release of various factors including antimicrobial peptides. To investigate the role of the midgut and internal tissues in the immune defense against gut-borne and systemic infections, we infected Manduca sexta larvae with B. thuringiensis ssp. kurstaki per os or injected Escherichia coli K12 into the hemocoel. We compared the immune response to both infection models by measuring mRNA levels of four immunity-related genes in the midgut, the fat body, the hematopoietic organs, and hemocytes as well as determined hemolymph antimicrobial activity. The midgut and circulating hemocytes exhibited a significantly increased level of lysozyme mRNA in response to gut infection but did not significantly alter expression in response to a systemic infection. Conversely, fat body and hematopoietic organs responded to both infections – gut-borne and systemic – by altered mRNA levels of at least one gene monitored. These data suggest that the gut recruits immune-related tissues in response to gut infection, even before systemic invasion, whereas systemic infections do not induce a response in the midgut. The experimental approach implies a skewed cross-talk: An intestinal infection triggers immune activity in systemic immune organs, but a systemic infection does not elicit any or only a very restricted immune response in the intestine. The hematopoietic organs (HOs) form and release hemocytes in larval M. sexta. We were able to broaden our understanding of the HOs in immunity since we demonstrate here that HOs i) synthesize lysozyme, and ii) respond to immune challenges by increased immune gene expression. These findings strongly suggest that the HOs not only provide phagocytes for the cellular immune response but also synthesize immunologically relevant humoral components, connecting both branches of the innate immune system.